1960
DOI: 10.1113/jphysiol.1960.sp006432
|View full text |Cite
|
Sign up to set email alerts
|

A study of presynaptic slow potentials in virus‐infected sympathetic ganglia of the rat

Abstract: In order to explain the occurrence of spontaneous impulses, originating in presynaptic nerve endings and discharged simultaneously and synchronously in pre-and post-ganglionic nerves of rat sympathetic ganglia infected with pseudo-rabies virus, the following working hypothesis was adopted. Spontaneous impulses originated in presynaptic nerve endings because the virus infection interfered with the normal action of an inhibiting system having its origin in the central nervous system (c.N.s.) and exerting its act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1962
1962
1982
1982

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Dempsher and his associates have shown that in the pathological condition resulting from infection with pseudorabies virus, spontaneous and synchronous postganglionic and antidromic preganglionic firing arises from the superior cervical ganglion (Dempsher and others, 1955), and that this is probably due to the action of ACh released from the presynaptic terminals (Dempsher and Riker, 1957). Furthermore, they have detected at both poles of such gangha slow waves of localised depolarisation, on which the propagated spikes are superimposed (Dempsher and Zabara, 1960) ; the former appear to represent typical generator potentials which have generally been thought to occur only at the postsynaptic side of the junction. It is possible that the mechanisms underlying these virusinduced phenomena are a combination of destruction of much of the presynaptic AChE, and extension centrally of the area of ACh-excitability of the axonal terminals, comparable to that which occurs distally at the sarcoplasmic membrane of skeletal muscle fibres after denervation (Axelsson and Thesleff, 1959).…”
Section: IVmentioning
confidence: 99%
“…Dempsher and his associates have shown that in the pathological condition resulting from infection with pseudorabies virus, spontaneous and synchronous postganglionic and antidromic preganglionic firing arises from the superior cervical ganglion (Dempsher and others, 1955), and that this is probably due to the action of ACh released from the presynaptic terminals (Dempsher and Riker, 1957). Furthermore, they have detected at both poles of such gangha slow waves of localised depolarisation, on which the propagated spikes are superimposed (Dempsher and Zabara, 1960) ; the former appear to represent typical generator potentials which have generally been thought to occur only at the postsynaptic side of the junction. It is possible that the mechanisms underlying these virusinduced phenomena are a combination of destruction of much of the presynaptic AChE, and extension centrally of the area of ACh-excitability of the axonal terminals, comparable to that which occurs distally at the sarcoplasmic membrane of skeletal muscle fibres after denervation (Axelsson and Thesleff, 1959).…”
Section: IVmentioning
confidence: 99%
“…Experimental. The experimental method has been described in detail elsewhere (Dempsher, Larrabee, Bang and Bodian, 1955;Dempsher, Tokumaru and Zabara, 1959;Dempsher and Zabara, 1960). Briefly, it is as follows:…”
Section: Methodsmentioning
confidence: 99%
“…However, it has also been clearly shown that curare blocks cholinergic sites in presynaptic terminals of sympathetic ganglia. (Dempsher and Riker, 1957;Dempsher and Zabara, 1960). The identity of the cholinergic receptor is not exactly known.…”
Section: The Role Of Matter {Structure) In the Bio-physical Basis Of mentioning
confidence: 99%